MemPavox: Computerized Program to Assess Visual-Verbal Working Memory - Sanz - Martin, A.; Gumá - Díaz, E.; Guevara, M. A.; Hernández - González, M. (Revista Mexicana de Ingenieria Biomedica, 2014)
Working memory is a temporary system that makes it possible to retain a certain amount of information and then manipulate and regulate it so as to guide behaviors and cognitive processes. PAVOX is a test that has been used in Mexico to evaluate visual verbal memory. In this test, the subject must remember the position of the semantic category of two- or three-syllable words presented randomly and consecutively on a computer monitor. This paper describes the operation and advantages of MemPavox, a computer program that was created according to the requirements of the PAVOX test. This program allows the presentation of words or any other visual stimulus while providing precise control of both time and the manner in which the stimuli appear, as well as the implementation of various stimulation paradigms, including the three tasks that make up the PAVOX test (vowel counting, categorization and dual). In addition, it records the type of response and subjects reaction times. Given its availability, flexibility and manageability, MemPavox can be used by both researchers in the field of cognitive neuroscience and professional psychologists to assess working memory.